Microeconomics of the rebound effect for residential solar photovoltaic systems - Matthew E. Oliver; Juan Moreno-Cruz; Ross C. Beppler (Center for Economic Studies and ifo Institute (CESifo), 2019)
The rebound effect is a well-known behavioral response whereby potential energy savings from efficiency improvements are partially offset by increased consumption of energy services, as the marginal cost of energy services is reduced. This paper characterizes a similar rebound effect related to installation and operation of a residential photovoltaic (PV) system. This solar rebound effect is different from traditionally studied rebound effects, primarily because it is due not to an improvement in the energy efficiency of a household's appliances, but to the supply of a zero-marginal-cost perfect substitute for grid electricity. The solar rebound effect is first derived in the absence of any subsidization mechanism. We then modify the model to account for two commonly implemented incentives: installation rebates and net metering. Rebates are shown to increase the rebound effect, whereas the effect of net metering depends on the per-unit compensation rate.
Keywords: Q41; Q42; Q48; 330; rebound effect; solar energy; residential photovoltaic systems; net metering; investment tax credit